Nouvelles données paléoenvironnementales dans le Sud de la France vers 30000 ans 14C BP : le cas de la grotte Marie (Hérault) - Crochet, Jean-Yves; Gence, Jean; Boulbes, Nicolas; Boutié, Paul; Cretin, Catherine; Crégut-Bonnoure, Évelyne; Duzer, Danièle; Jolly, Dominique; Laudet, Frédéric; Lefévre, David; Mourer-Chauviré, Cécile; Rousselières, France; et al. (Comptes Rendus Palevol, 2007)
The Marie cave, discovered to the north of Montpellier, Herault (France), has yielded a fauna of 28 vertebrates, out of which 23 are small ´ to large mammals, notably Mammuthus primigenius. The few discovered artefacts have been attributed to the Upper Palaeolithic, which is in agreement with the two radiocarbon dates (31450 14 C yr BP for the low level, and 28680 14 C yr BP near the cave’s entrance). The palynological study shows the existence (i) of a wooded steppe on the plateau, and (ii) of a riverine forest with alders in the valleys, associated with Mediterranean taxa. These data conﬁrm the presence in Languedoc of Mediterranean species around 30000 yr BP, which qualiﬁes the hypothesis of exclusively Spanish and Italian refuges during glacial periods
Keywords: France; Marie cave; Palaeoenvironment; palynology; Upper Palaeolithic; Vertebrates; Wurm

Nouvelles données paléoenvironnementales dans le Sud de la France vers 30000 ans 14C BP : le cas de la grotte Marie (Hérault) - Crochet, Jean-Yves; Gence, Jean; Boulbes, Nicolas; Boutié, Paul; Cretin, Catherine; Crégut-Bonnoure, Évelyne; Duzer, Danièle; Jolly, Dominique; Laudet, Frédéric; Lefévre, David; Mourer-Chauviré, Cécile; Rousselières, France; et al. (Comptes Rendus Palevol, 2007)
The Marie cave, discovered to the north of Montpellier, Herault (France), has yielded a fauna of 28 vertebrates, out of which 23 are small ´ to large mammals, notably Mammuthus primigenius. The few discovered artefacts have been attributed to the Upper Palaeolithic, which is in agreement with the two radiocarbon dates (31450 14 C yr BP for the low level, and 28680 14 C yr BP near the cave’s entrance). The palynological study shows the existence (i) of a wooded steppe on the plateau, and (ii) of a riverine forest with alders in the valleys, associated with Mediterranean taxa. These data conﬁrm the presence in Languedoc of Mediterranean species around 30000 yr BP, which qualiﬁes the hypothesis of exclusively Spanish and Italian refuges during glacial periods
Keywords: France; Marie cave; Palaeoenvironment; palynology; Upper Palaeolithic; Vertebrates; Wurm

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology

Santa Lucia superiore (Toirano, Ligurie) : reconstitution locale de la végétation ligure durant le Pléniglaciaire ancien - Kaniewski, David; Renault-Miskovsky, Josette; Tozzi, Carlo; de Lumley, Henry (Geobios, 2005)
Pollen analysis of Santa Lucia superiore cave (Italy) reports at local scale the lowland Ligurian vegetation during the Lower Pleniglacial (75 to 57 Kyr BP). The pollen proﬁle shows two AP extensions during a steppe-landscape episode in Liguria. The dry and cold phases caused the establishment of a steppe-landscape (NAP 92%) with Artemisia, Ephedra, Poaceae and Chenopodiaceae, similar to those mentioned in the Latium during the Pleniglacial. The increase of moisture generated a ﬁrst arboreal extension (Pinus, Betula, Corylus, Ulmus), which engendered the formation of an open-forest landscape (AP 43%). The second arboreal extension (AP 55%) was due to an increase of moisture and higher temperatures, which allowed the development of Mediterranean trees and shrubs (Quercus ilex, Olea, Phillyrea). This warming up occurred probably simultaneously with a secondary transgression during the glacial sea-level change. The upper part of the proﬁle shows an open vegetation, which indicates the return of a steppe-landscape. Pollen data, replaced in the multidisciplinary studies of the site, are well correlated with the fauna and sediment data.
Keywords: Full glacial; Liguria; Middle Palaeolithic; palynology; Prehistory; Upper Pleistocene

Vegetation dynamics in north-western Mediterranean regions: Instability of the Mediterranean bioclimate - De Beaulieu, J.-L.; Miras, Y.; Andrieu-Ponel, V.; Guiter, F. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Pollen and plant macrofossil records from a selection of sites in Spain, France and Italy are used to explore the origin and the development of the Mediterranean vegetation. The role of evergreen and summergreen taxa is discussed. The expansion of sclerophyllous trees during the Pleistocene interglacials is well correlated with the orbital forcing. During the Holocene, the large number of data illustrates latitudinal and longitudinal differences in vegetation dynamics. Multidisciplinary studies identify short terms climatic fluctuations. The debate is still open between those who attribute an increase of sclerophyllous forests during the late Holocene to a trend toward aridity and those who consider this dynamic as human-induced.
doi: 10.1080/11263500500197858doi: 10.1080/11263500500197858The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: human impact; Mediterranean ecosystems; palaeoclimates; palynology; review

Madonna dell'Arma (San Remo, Italie) : expression locale de la végétation ligure au cours du Paléolithique moyen - Kaniewski, David; Renault-Miskovsky, Josette; de Lumley, Henry (Geobios, 2004)
Pollen analysis of Madonna dell’Arma cave inside part (Liguria, Italy) allowed us to reconstitute, at local scale, the Ligurian coastal vegetation between the end of the last interglacial period and the beginning of the pleniglacial. This transition period shows an important representation of arboreal cover and a persistence of thermophilous elements that allowed us to considerate the western Liguria as a periglacial refuge. During the end of the last interglacial, xerophytic, halophytic herbs and shrubs taken over from a Mediterranean pre-forest unit in the ﬁrst slopes constituted the coastal zone. The nearness ofArgentina torrent and theArmea inﬂuenced, in the coast, the existence of marshy zones colonized by hygrophilous trees. In the Ligurian lowlands spread out sclerophyllous and mesophilous forests according to altitude. The beginning of the pleniglacial is indicated in the sequence by increases of Pinus, Cupressaceae and Artemisia in the context of a decline in the thermophilous components. This picture of vegetation has become integrated into the multidisciplinary studies of the site and contributed to the elaboration of palaeoclimatic hypothesis similar as those revealed by the fauna.
Keywords: Interglacial; Liguria; Middle Palaeolithic; palynology; Pleniglacial; Prehistory; Upper Pleistocene

Sclerophyllous vegetation dynamics in the north of the Iberian peninsula during the last 16,000 years - RAMIL-REGO, P; RODRÍGUEZ-GUITIÁN, M; MUÑOZ-SOBRINO, C (Global Ecology and Biogeography, 1998)
We used pollen analysis to evaluate the dynamics of sclerophyllous arboreal taxa during the last 16,000 years. Quercus ilex type pollen and, to a lesser degree, other sclerophyllous elements (e.g. Olea and Phillyrea) have been documented during the Late-glacial in the majority of the sequences obtained in continental territories in the north of the Iberian peninsula, as well as in the eastern coastal/sub-coastal area in the Cantabric region. During the Late-glacial and the Holocene, sclerophyllous elements became widespread in many areas of the north Iberian peninsula (the Sil, Duero and Ebro depressions and the southernmost slopes of adjacent mountains), with the smallest pollinic representation of these taxa being for the most septentrional areas (coastal/sub-coastal territories and the northermost slopes of the Cantabrian-Atlantic Mountains). During these periods, there is no indication of the presence of Quercus ilex pollen in the northwestern territories, which would explain the absence of this species in the present-day landscape. Despite the widespread distribution that sclerophyllous elements have maintained during the last 16,000 years, they have never attained a predominant role in the landscape, having a smaller representation, both during hotter and colder phases, than deciduous forests, pine forests and mixed forests.
Keywords: Holocene; iberian peninsula; Late-glacial; palynology; Quercus ilex; sclerophyllous forests; species range; vegetation history

Palynology of the 112.8–197.8 m interval of the core Tenaghi Philippon III, Middle Pleistocene of Macedonia - Van Der Wiel, A M; Wijmstra, T A (Review of Palaeobotany and Palynology, 1987)
In this article the palynological record of the Tenaghi Philippon III core (112.8–197.8 m) from the Philippi Plain in Greece is discussed. The arboreal pollen diagrams show an alteration of steppe phases (representing glacial periods) and oak forest phases (coinciding with interglacial periods). A proposal for a local biostratigraphy is given and a preliminary correlation is suggested with the Northwest European subdivision of the Middle Pleistocene. From the AP diagrams it appears that the flora is gradually impoverished in Arcto-Tertiary elements and obtains a more mediterranean character. In this section, however, the real mediterranean forest, rich in Quercus ilex/coccifera type is not yet present, which implies that a warm humid climate dominated with rainfall throughout the year. The presence of a great number of Tertiary pollen, two sterile intervals and clastic sediment in the lower part of the core, while from 181.6 m upwards organic sediment is found, indicates a change in sedimentation regime around a depth of 182 m. The sedimentation regime changed from fluvatile to lacustrine as a result of the aftermath of tectonic events. Chronostratigraphy of the diagrams is based on radiocarbon dates from the TF2 core, paleomagnetic polarity determinations in the TF3 core as well as interpolations between the two. In this way the core was dated at 900,000-approx. 600,000 yr B.P. A correlation with deep-sea Core V28–239 is proposed. From this correlation it appears that both in the diagrams and in the oxygen isotope curve the glacial and interglacial periods of the Middle Pleistocene are of a different wavelength and amplitude as compared to the ones of the Upper Pleistocene.
Keywords: Biostratigraphy; Chronostratigraphy; palynology; vegetation history (PG)